1957
DOI: 10.1017/s0373463300017008
|View full text |Cite
|
Sign up to set email alerts
|

The Mathematics of Collision Avoidance at Sea

Abstract: i. INTRODUCTION. Of the many factors affecting the collision problem, the mathematics of relative motion is the one most susceptible to formal analysis. Moreover, this 'collision geometry' must form the basis of any investigation into the instrumental, operational and human factors involved. It is therefore surprising that no complete description of the (mathematically) simple relationships is readily available. The object of this paper is to present such a connected account of the mathematics of relative mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1964
1964
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The basis of the positional game involves assigning the maneuver strategy of the own object to the current positions of p ( t k ) objects in the current step k . As such, the process model considers all possible changes in the course and speed of the encountered objects during the control [26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42] (Figure 2).…”
Section: The Safe and Game Object Control In Autonomous Ship Navigmentioning
confidence: 99%
“…The basis of the positional game involves assigning the maneuver strategy of the own object to the current positions of p ( t k ) objects in the current step k . As such, the process model considers all possible changes in the course and speed of the encountered objects during the control [26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42] (Figure 2).…”
Section: The Safe and Game Object Control In Autonomous Ship Navigmentioning
confidence: 99%
“…To give an idea of the numerical magnitudes of p and rj, we may quote Sadler's figures, 5 namely p = o-o3 (a 3 per cent error), and •q =0-03 (a 2° bearing error, four times as much as that assumed by Parker" or WylieS). Whatever may be their actual size, if p and 17 are of the same order of magnitude, formula (1) shows that, provided mjry and m\r 2 are fairly small (say, less than i/y), range errors make a negligible contribution compared with that made by bearing errors.…”
Section: Ww+rt + Wtf (I)mentioning
confidence: 99%
“…At a meeting of the Technical Committee of the Institute 1 held on 9 January 1963 it was suggested that recent theoretical treatments of the collision problem 2 . The basic mathematical relations for near-miss encounters have been set out in this Journal on several occasions, notably by Sadler 5 and Morrell,6.7 and in graphical form by Wylie.8 The recent paper by Parker* 1 deals with the effects of both systematic and random errors of radar observations of relative range and bearing. * could usefully be extended to include a discussion of the near-miss situation and the effect of observational errors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the management of such processes is accomplished by means of game control systems, whose synthesis is carried out with the methods of game theory [9,10]. Game theory is a branch of mathematics, covering the theory of conflict situations and building and analyzing their models [11,12]. Conflict can be as follows: military, political, social, and economic, in a social game, in the game with nature, and in the implementation of the control process during interferences of disturbances or other control objects [13].…”
Section: Introductionmentioning
confidence: 99%